Influence of Accelerated Aging on the Color Stability of Dental Zirconia - Maziero Volpato, Claudia Angela; Cesar, Paulo Francisco; Bottino, Marco Antonio [UNESP] (Wiley-Blackwell, 2016)
ObjectiveThis study evaluated the influence of different aging times on the color stability of zirconia that is either veneered or not by ceramic. Materials and MethodsFifteen zirconia disks (3Y-TZP) were produced (12.0 mm in diameter and 1.0 mm-thick). Five disks (G1) did not receive veneering ceramic layer; 5 disks (G2) were veneered with 1.0 mm a ceramic layer and the other 5 disks (G3) were veneered with layer of 1.5 mm. The L*a*b* coordinates (T1) were measured with a spectrophotometer. The disks were subjected to an accelerated aging protocol for 1 hour (T2), 2 hours (T3) and 4 hours (T4). Measurements were made after each aging time. Differences in color (E00), lightness (L), chroma (C), and hue (H) were calculated by CIEDE2000 color difference formula among standard-averages, aging times and thickness tested. For E-00, one-way ANOVA was performed for the G1 and two-way ANOVA for G2 and G3. Repeated measures ANOVA was performed for L, C, and H. Multiple comparisons were performed using Tukey's test (=0.05). ResultsFor G1, statistical differences were found for lightness (L), chroma (C), and hue differences (H) (p=0.0001), highlighting the major in chroma differences (C). Discrete color differences (E-00) were observed (0.95E(00)) especially after 4 hours of aging (T4). For G2 and G3, statistical differences for L, C, and H were found as a function of the thickness of the ceramic coating (p<0.0001) and aging time (p=0.02). ConclusionsWhen 3Y-TZP was subjected to aging, discrete color differences were present. With exception of the G2, the color difference was less than 1.25E(00), demonstrating that the zirconia maintained its colorimetric properties after aging protocol. CLINICAL SIGNIFICANCEAfter prolonged aging, discrete color changes can occur in zirconia, particularly when it is contact with the oral environment, as is the case of abutments and monolithic crowns. Thus, clinical and laboratory care should be taken to maintain surface integrity of zirconia, minimizing aging. (J Esthet Restor Dent 28:304-312, 2016)